Samuel Beckett and Disability Performance. Issue 1 (April 2021) - Simpson, Hannah
Abstract : Beckett's plays have attracted a striking range of disability performances, in part because of their insistent attention on embodied existence and the impaired body. Here, I examine four recent disability performances of Beckett's plays, exploring how these productions prompt re-evaluation of the previously undetected indicators of disability in the scripts, including mobility impairment, automatic speech, stuttering, and memory deficiency. Drawing on a series of original interviews with the practitioners in question, I examine the intersection between textual aesthetics and disability ethics in these contemporary productions, emphasising how these performances illuminate crucial corporeal, social, and ontological concerns in Beckett's original scripts, in newly embodied terms.